The effect of microfinance factors on women entrepreneurs’ performance in Nigeria: a conceptual framework - Razli Che Razak; Isidore Ekpe; Norsiah Mat (2011)
Women play a crucial role in the economic development of their families and communities but certain obstacles such as poverty, unemployment, low household income and societal discriminations mostly in developing countries have hindered their effective performance of that role. As such, most of them embark on entrepreneurial activities to support their families. It is discovered that women entrepreneurship could be an effective strategy for poverty reduction in a country; since women are the worst hit in such situation. However, it is discovered that women entrepreneurs, especially in developing countries, do not have easy access to microfinance factors for their entrepreneurial activity and as such have low business performance than their men counterparts, whereas the rate of their participation in the informal sector of the economy is higher than males, and microfinance factors could have positive effect on enterprise performance. The objective of this study is to examine the effect of credit, savings, training and social capital on women entrepreneurs’ performance in Nigeria. The study involves a survey using structured questionnaire and an indepth interview to solicit responses from women entrepreneurs, and secondary data from microfinance institutions. Data analysis involves the use of Structural Equation Modelling.